"And you will wait …": Carceral transportation in electronic monitoring as part of the punishment process. (January 2021) - Eife, Erin; Kirk, Gabriela
Electronic monitoring, often accompanied with house arrest, is used extensively across the United States as a means of pretrial supervision and as a condition of probation and parole. In this article, we bridge the literatures of procedural punishment and carceral geography to detail how this previously understudied process of transport from jail to electronic monitoring serves not just as a necessary bureaucratic process, but as a key moment of punishment and power. Utilizing in-depth interviews with 60 people who were currently or recently on EM in Cook County, IL, we argue that this moment of transport is itself a punitive experience. We find that sheriff's officers involved in the transport process punish individuals through the manipulation of time and space, verbal threats, and infantilization. This punishment in transport instills a subjugated status that sets the tone for the EM experience, aiding in reinforcing the home as the new carceral space.